Depressão: uma breve revisão dos fundamentos biológicos e cognitivos - Saint-Clair Bahls (Interação em Psicologia, 1999)
The relevance of depression in the clinical context is considerably well known for its ability to impose significant restrictions on and harm to individuals, families and society. The treatment of this condition has broadened and increasingly specific therapeutic resources have been defined, with regard to both its biological and psychological aspects, which often need to be dealt with together in order to achieve more satisfactory results. Existing treatments are based on theoretical suppositions and also contribute towards the development of some aetiological hypotheses regarding this illness. The author of the article reviews the biological and cognitive fundaments relating to depression.